The Victorians’ Opioid Epidemic - Susan S., Nash, (IJRDO - Journal of Social Science and Humanities Research, 2018)
They had one at home. They caused one in China. And, they spawned mono-economies in Afghanistan, corruption in the ports, and vast networks of shipping, financing, and service companies all founded on the medicinal properties, but above all, the miraculously addictive properties of opium (Diniejko, 2002). Victorians of the British Empire had their own opioid epidemic and opium trading of truly global extent, with repercussions that persist even into our own times.